Genetic Characterization of Caesio cuning (Bloch, 1791) Using COI Gene Markers in the Marine Waters of North Maluku and North Sulawesi - Marsaoly, Muh. Rafil Afdalul Firkan; Rondonuwu, Ari Berty; Lintang, Rosita Anggreiny. J; Wullur, Stenly; Rangan, Jety Kornela; Undap, Suzanne Lydia (Jurnal Ilmiah PLATAX, 2025)
This research investigates the genetic composition of C. cuning (Bloch, 1791) inhabiting the coastal waters of North Maluku and North Sulawesi through the application of DNA barcoding, utilizing the mitochondrial COI (Cytochrome c Oxidase subunit I) gene as a molecular marker. Specimens were obtained from four distinct sampling sites: Ternate, Guraping, Ratatotok, and Manado. DNA was extracted using a commercially available kit, followed by amplification via PCR and sequence analysis using the MEGA X platform. Sequencing results produced a 611 bp fragment of the COI gene, with a nucleotide profile dominated by pyrimidine bases—specifically thymine and cytosine. Genetic similarity between local samples and GenBank references ranged from 99.08% to 100%, indicating a high level of genetic uniformity. Phylogenetic reconstruction showed that populations from the four locations clustered with C. cuning populations from other western Indo-Pacific regions, including East Java, Bali, and the Philippines. These findings support the recognition of C. cuning in the study area as a single, genetically cohesive stock suitable for regionally coordinated conservation and sustainable fishery management. Keywords: C. cuning, COI gene, DNA barcoding, genetic structure, phylogenetic analysis. Abstrak Penelitian ini mengkaji komposisi genetik ikan C. cuning (Bloch, 1791) yang tertangkap erairan pesisir Maluku Utara dan Sulawesi Utara melalui pendekatan DNA barcoding dengan menggunakan gen mitokondria COI (Cytochrome c Oxidase subunit I) sebagai penanda molekuler. Spesimen dikumpulkan dari empat lokasi sampling yang berbeda, yaitu Ternate, Guraping, Ratatotok, dan Manado. Ekstraksi DNA dilakukan menggunakan kit komersial, dilanjutkan dengan amplifikasi melalui PCR serta analisis sekuens menggunakan perangkat lunak MEGA X. Hasil sekuensing menghasilkan fragmen gen COI sepanjang 611 bp, dengan komposisi nukleotida yang didominasi oleh basa pirimidin—khususnya timin dan sitosin. Tingkat kemiripan genetik antara sampel lokal dan referensi dari GenBank berkisar antara 99,08% hingga 100%, menunjukkan tingkat homogenitas genetik yang tinggi. Rekonstruksi filogenetik memperlihatkan bahwa populasi dari keempat lokasi tergabung dalam satu klade dengan populasi C. cuning dari wilayah lain di Indo-Pasifik bagian barat, termasuk Jawa Timur, Bali, dan Filipina. Temuan ini mendukung pengakuan bahwa C. cuning di wilayah studi merupakan satu stok genetik yang kohesif dan sesuai untuk dikelola secara kolektif dalam upaya konservasi serta pengelolaan perikanan berkelanjutan di tingkat regional. Kata kunci: C. cuning, gen COI, DNA barcoding, struktur genetik, analisis filogenetik